Inclusion properties for certain classes of differential subordination - Ma`moun Harayzeh Al-Abbadi,; Maslina Darus, (Penerbit ukm, 2009)

(untitled)
In this work, we introduce a new generalised derivatives operator µ n,m. By using this operator, we introduce several new subclasses of analytic function defined in the open unit disc U = {z € C:|z|<1}. We also investigate various inclusion properties of these subclasses. In addition, we determine inclusion relationships between these new subclasses and other known classes.